A Research on The Improvement of Persuasive Writing Skill of Sixth Grade Students in Secondary School - (:unkn) unknown (TURKISH EDUCATION ASSOC, 2018)
Today's communication possibilities bring along directive communication. Certain groups, institutions, or people can use communication to persuade for their special purposes. When Turkish main language curriculums were examined, even though the persuasive writing takes place at the elementary school level, it does not take place at the secondary school level. Contrary to this situation in Turkey, in the main language curriculums of many countries such as South Korea, China Hong-Kong, Singapore, Canada, Ireland, Australia, and the USA there is a systematic and important place at elementary and secondary school level for persuasive writing. In this research, moving from the lack of this writing skill at secondary school level, an action research process based on the question How can the persuasive writing skills of 6th-grade students in secondary school be improved in Turkish lesson? was carried out. For this purpose, a persuasive writing education program was prepared using a process - based writing model. This program was applied 15 weeks (34 class hours) in a class of 18 students and the effect of the program on the students was followed. Research questions are as follows: 1. What is the opinion of students about persuasion before persuasive writing education? 2. What is the effect of persuasive writing education on the ability of students to create the persuasive text? 3. How is the relationship between persuasive text analysis and persuasive text creation? 4. What are the views of students about persuasive writing education? 5. What are the problems encountered in the research process? The data in the study were obtained from student products, evaluation rubric for persuasive text, analysis texts, checklist, student and researcher diary. In data analysis SPSS 23 and NVivo-11-Pro programs were used. In the direction of the findings, text creation and text analysis ability of 6th-grade students developed these skills. Moreover, it was seen that students did not succeed at the expected level in applying counter opinions and source items of persuasive expression in the process of text creation and text analysis, and there was no significant progress with the education process in spelling and punctuation. On the other hand, it has been found that students are good level for elaboration, transition words and very good level for title, introduction, development, result, thesis, supporting opinions, emotional orientation, repeat, call, justification, requirement statements. After analyses of researcher and student diaries, the themes have been reached that can increase productivity in education.
Keywords: Language skills; Writing skills; Persuasive writing; Action research; Sixth grade